2015
DOI: 10.1017/s0022109015000551
|View full text |Cite
|
Sign up to set email alerts
|

Lending Relationships and the Effect of Bank Distress: Evidence from the 2007–2009 Financial Crisis

Abstract: We study the transmission of bank distress to nonfinancial firms from 34 countries during the 2007-2009 financial crisis using systemic and bank-specific shocks. We find that bank distress is associated with equity valuation losses and investment cuts to borrower firms with the strongest lending relationships with banks. The losses are not offset by borrowers' access to public debt markets and are concentrated in firms with the greatest information asymmetry problems and weakest financial positions. Our findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 58 publications
(57 reference statements)
0
28
2
Order By: Relevance
“…Another prominent research stream is access to capital and changes in investment during financial crises (Campello et al, 2011;Kahle and Stulz, 2013). Other interesting emerging topics are the effect of regulatory risk on markets (Pastor and Veronesi, 2013), the prospects of strategic default by borrowers (Favara et al, 2012), the transmission of bank distress to nonfinancial firms (Carvalho et al, 2015), the link between bank competition and financial stability (Akins et al, 2014), cross-market transmission of risk (Bekaert et al, 2014) and formative experience and portfolio choice around the Finnish great depression (Knüpfer et al, 2017).…”
Section: Financial Crisesmentioning
confidence: 99%
“…Another prominent research stream is access to capital and changes in investment during financial crises (Campello et al, 2011;Kahle and Stulz, 2013). Other interesting emerging topics are the effect of regulatory risk on markets (Pastor and Veronesi, 2013), the prospects of strategic default by borrowers (Favara et al, 2012), the transmission of bank distress to nonfinancial firms (Carvalho et al, 2015), the link between bank competition and financial stability (Akins et al, 2014), cross-market transmission of risk (Bekaert et al, 2014) and formative experience and portfolio choice around the Finnish great depression (Knüpfer et al, 2017).…”
Section: Financial Crisesmentioning
confidence: 99%
“…Furthermore, their evidence indicates that constrained firms report significantly larger planned percentage cuts compared to their peers in technology and capital spending and employment. Carvalho et al (2015) show that the 2007-2009 financial crisis is associated with equity valuation losses and investment cuts to borrower firms with the strongest lending relationships with banks. Almeida et al (2011) reveal that US firms whose long-term debt was largely maturating immediately after the third quarter of 2007 cut their investment-to-capital ratio more than other similar firms whose debt was due well after the crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the average percentage of 1 Most of this literature has focused on the influence of the financial crisis within the US context (Almeida et al, 2011;Duchin et al, 2010;Ivashina and Scharfstein, 2010;and Santos, 2011, among others). The exception are the papers by Campello et al (2010), Carvalho et al (2015) and Lins et al (2013), which analyse the impact of the crisis on real decisions made by corporations in an international context. long-term debt for firms in South Korea, the USA and India decreased 7 per cent during the crisis compared to average values prior to 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Authors suggest the necessity of cooperation between central banks and micro prudential supervision. Carvalho et al, 2015, concluded that, in a crisis period, bank distress results in the cutting of loans towards firms, especially those in the weakest financial position. Gauvin, 2014, concluded that in a crisis period, the less capitalized and less liquid banks display more cyclical behavior.…”
Section: Previous Resultsmentioning
confidence: 99%